PENGARUH VARIABEL MONETER TERHADAP PERTUMBUHAN EKONOMI INDONESIA SEBELUM DAN SAAT PANDEMI COVID-19 - D Arieffandy; A.S Fitria; F.H Putri; D.D Julia (Jurnal Pendidikan Ekonomi Indonesia, 2020)
The development of the monetary sector is one way to increase the rate of economic growth. This study aims to analyze the impact of monetary variables on Indonesia's economic growth before and during the Covid-19 pandemic. This study uses secondary data in the form of time series data from free money supply, interest rates, inflation, exchange rates, and Indonesia's economic growth before the pandemic, namely from 2000 - 2019 (y-to-y) and during the pandemic, namely in 2020. (q-to-q) obtained from data published by Bank Indonesia in the form of Monetary Economic Statistics, Monetary Policy Reports, Indonesian Economic Reports, and the Central Statistics Agency. From the results of the research conducted, it was found that the inflation rate and interest rates in Indonesia have a positive effect on economic growth, while the money supply with exchange rates does not have a positive effect on economic growth in Indonesia.